Tobacco related knowledge and support for smoke-free policies among community pharmacists in Lagos state, Nigeria - Poluyi EO; Odukoya OO; Aina BA; Faseru B (Centro de Investigaciones y Publicaciones Farmaceuticas, 2015)
Background: There are no safe levels of exposure to second hand smoke and smoke-free policies are effective in reducing the burden of tobacco-related diseases and death. Pharmacists, as a unique group of health professionals, might be able to play a role in the promotion of smoke-free policies. Objective: To determine the tobacco-related knowledge of community pharmacists and assess their support for smoke-free policies in Lagos state, Nigeria. Methods: A cross-sectional descriptive study design using both quantitative and qualitative methods was employed. Two hundred and twelve randomly selected community pharmacists were surveyed using a pre-tested self-administered questionnaire. In addition, one focus group discussion was conducted with ten members of the Lagos state branch of the Association of Community Pharmacists of Nigeria. Results: The quantitative survey revealed that the majority (72.1%) of the respondents were aged between 20 and 40 years, predominantly male (60.8%), Yoruba (50.2%) or Igbo (40.3%) ethnicity and had been practicing pharmacy for ten years or less (72.2%). A majority (90.1%) of respondents were aware that tobacco is harmful to health. Slightly less (75.8%) were aware that second hand smoke is harmful to health. Among the listed diseases, pharmacists responded that lung (84.4%) and esophageal (68.9%) cancers were the most common diseases associated with tobacco use. Less than half of those surveyed associated tobacco use with heart disease (46.9%), chronic obstructive pulmonary disease (27.8%), bladder cancer (47.2%), peripheral vascular disease (35.8%) and sudden death (31.1%). Only 51.9% had heard of the World Health Organization Framework Convention on Tobacco Control (WHO FCTC). A little over half of the respondents (53.8%) were aware of any law in Nigeria controlling tobacco use. The majority of respondents supported a ban on smoking in homes (83.5%), in public places (79.2%), and in restaurants, nightclubs and bars (73.6%). For every additional client attended to daily, knowledge scores increased by 0.022 points. Current smokers were 1.3 times less likely to support smoke-free policies compared with non-smokers. The findings emanating from the focus group discussion reinforced the fact that the pharmacists were in support of smoke-free policies particularly in homes and public places. It also demonstrated that most of them were aware of the health risks associated with tobacco use and second hand smoke however some misconceptions seemed to exist. Conclusion: The pharmacists surveyed expressed support of smoke-free policies and most of them were aware of the health risks associated with tobacco use. However, awareness of WHO FCTC and country-level tobacco legislation was low. Current smokers were less likely to support smoke-free policies. Community pharmacists should therefore be considered worth engaging for the promotion of smoke-free policies. Efforts should also be made to educate pharmacists about country level smoke-free laws.